Partial ring hydrogenation of naphthols over supported metal catalysts in supercritical carbon dioxide solvent - Mine, Eiichi; Haryu, E.; Arai, K.; Sato, T.; Sato, O.; Sasaki, A.; Rode, C. V.; Shirai, M. (Chemistry Letters, 2005)
Selective ring hydrogenation of naphthols to tetrahydronaphthols and tetralones proceeded at 323 K over a charcoal supported rhodium catalyst in supercritical carbon dioxide.